1983
DOI: 10.1044/jshr.2604.568
|View full text |Cite
|
Sign up to set email alerts
|

Direct Magnitude Estimation and Interval Scaling of Stuttering Severity

Abstract: The appropriateness of direct magnitude estimation and interval scaling for assessing stuttering severity was investigated by determining whether the continuum of the stutterers' judged severity was prothetic or metathetic. As operationally defined by Stevens, prothetic continua show a curvilinear relation between magnitude estimates and interval scale values of the same set of stimuli, whereas metathetic continua show a linear relation between these scale values. The stuttering severity of 20 stutterers was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
0
19
1
Order By: Relevance
“…They concluded that although both scales were of similar sensitivity in detecting changes in treatment, the Likert scale was preferred as the authors presumed it was easier to use than the VA scale. However, while personal preference or usability serves a role in the selection of an appropriate rating scale, decisions should be made in conjunction with systematic evaluation of both validity and reliability in measuring the nature to be scaled [19] .…”
Section: Scaling Voice Activity and Participationmentioning
confidence: 99%
“…They concluded that although both scales were of similar sensitivity in detecting changes in treatment, the Likert scale was preferred as the authors presumed it was easier to use than the VA scale. However, while personal preference or usability serves a role in the selection of an appropriate rating scale, decisions should be made in conjunction with systematic evaluation of both validity and reliability in measuring the nature to be scaled [19] .…”
Section: Scaling Voice Activity and Participationmentioning
confidence: 99%
“…Seemingly they also did not find any difference regarding the degree of difficulty encountered when answering the questionnaire. On the other hand, as far as the time of answering the questionnaire is concerned, the NS scale provided a faster rating (9,12) . Probably, the continuous line of the VAS, which does not have category or division support, make the individuals insecure during the rating.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of the type of scale must be based on practical considerations, on the individual preferences and on the feasibility of its use in the clinical routine taking into account the time of administration (3,4,9) . In the present study, both scales produced similar results as it happened to the Chinese study (11) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations